Public Transport in Developing Countries - Adinata, Rendra; Wike, Wike; Wanto, Alfi Haris (JPAS (Journal of Public Administration Studies), 2021)
The changes and challenges in public transport in developing countries are need to be address with the right policy, yet to make the right policy, we need to identify the main problem and characteristics of public transport in developing countries itself. This article explain the characteristics of public transportation in developing countries using literature review. In general, it is based on its organization, multimodal transport planning and finance, fare control, fare exemptions and social obligations, vehicle specifications, competition and regulation and finally ownership and investment.